The effect of 222‐nm UVC phototesting on healthy volunteer skin: a pilot study. Issue 3 (15th January 2015) - Woods, Julie A; Evans, Alan; Forbes, Paul Donald; Coates, Philip J; Gardner, June; Valentine, Ronan M; Ibbotson, Sally H; Ferguson, James; Fricker, Christopher; Moseley, Harry
Abstract: Background: Frequent topical antiseptic use to hands is now common in healthcare and other work environments. Inevitably, the use of such antiseptics will present an occupational risk for irritancy and allergic dermatitis. New, less irritant and even non‐chemical antimicrobial approaches are under investigation. Methods: A Sterilray disinfectant source (222 nm) conventionally used to sterilize equipment and work surfaces was assessed for tolerability in human skin. Using an escalating dosage study methodology, four skin phototype I and II healthy volunteers had their minimal erythema dose (MED) determined. Punch biopsies of irradiated sites were stained for cyclobutane pyrimidine dimers (CPD). The degree of CPD was compared with that in biopsies from unexposed skin and from areas exposed to UVB (280–315 nm) radiation. Results: Calibrated spectral measurements revealed emission at a peak wavelength of 222 nm with 97% emission at wavelengths less than 250 nm. At low doses below the threshold bacteriostatic effect, the source was capable of inducing both erythema and CPD formation in human skin. In two individuals, cells in the basal layer were not shielded by the overlying tissue as indicated by the presence of CPD. Conclusion: The source showed an erythemogenic or CPD potential at lower doses than those required to reach the reported threshold bacteriostatic effect.